mTORC1 and mTORC2 regulate skin morphogenesis and epidermal barrier formation - Xiaolei Ding (Nature Portfolio, 2016)
mTOR regulates cell growth via a protein complex including mTORC1 and mTORC2, but their role in skin morphogenesis is unclear. Here, the authors delete mTORC1 and mTORC2 from the epidermis and see epidermal deficiencies but both mTORCs play distinct roles in skin morphogenesis.